2020
DOI: 10.3390/jcm9082483
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Apolipoprotein B48 is Associated with Subclinical Atherosclerosis in Patients with Rheumatoid Arthritis

Abstract: Objective: To describe postprandial lipemia in patients with rheumatoid arthritis (RA) and to analyze its association with subclinical atherosclerosis measured as carotid intima-media thickness (cIMT). Methods: We performed an observational study of 40 patients with RA and 40 sex and age-matched controls. Patients with dyslipidemia were excluded. Pathologically increased cIMT was defined as a carotid thickness greater than the 90th percentile (>p90) for age and sex. Fasting and postprandial plasma lipids, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 60 publications
(64 reference statements)
2
8
1
Order By: Relevance
“…The rates of RF and anti-CCP positivity and radiological erosions were similar to those reported in other Spanish series of patients with RA [ 35 , 36 ]. On the other hand, we did not find significant associations between these factors and the CIMT, which have been observed in smaller cohorts [ 33 , 37 ]. Regarding acute-phase reactants, as in other research [ 38 ], a correlation was observed between ESR and CIMT.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…The rates of RF and anti-CCP positivity and radiological erosions were similar to those reported in other Spanish series of patients with RA [ 35 , 36 ]. On the other hand, we did not find significant associations between these factors and the CIMT, which have been observed in smaller cohorts [ 33 , 37 ]. Regarding acute-phase reactants, as in other research [ 38 ], a correlation was observed between ESR and CIMT.…”
Section: Discussioncontrasting
confidence: 92%
“…On the other hand, while there was a trend towards a larger CIMT, the differences did not reach statistical significance. This finding has also been reported in previous studies [ 33 ] and may be due to the relatively low inflammatory activity in our patients, which might have had a beneficial effect on CIMT. Other research has demonstrated that effective control of the disease may abrogate any specific effect on RA on atherosclerosis progression [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…We defined PPHL as postprandial triglycerides >220 mg/dL and/or postprandial ApoB48 levels greater than the 75th percentile (>p75) [14]. The highest postprandial ApoB48 values reported to date in patients with RA were those previously published by our group [15]. Burggraaf et al [16] also reported that patients with RA had higher baseline ApoB48 levels than controls and that the accumulation of atherogenic chylomicron remnants could contribute to the risk of cardiovascular events in affected patients.…”
Section: Discussionmentioning
confidence: 88%
“…In a previous study [ 15 ], we observed that patients with RA experienced a more marked increase in postprandial lipidemia than healthy controls and that ApoB48 levels were associated with cIMT. However, the factors associated with this increase in ApoB48 were not analyzed because they were not the objective of the study.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation